The public sector in Japan : Past developments and future prospects - Doi, Takero (Edward Elgar Publishing, 2009)
The book explores many of the important issues facing Japan's economy during the past three decades.Topics such as social security, the aging of society, demographic change, public finance, deregulation, and government debt are brought to the fore in a readable account backed up with thoroughly researched empirical examples.